2018
DOI: 10.1371/journal.pone.0195408
|View full text |Cite
|
Sign up to set email alerts
|

High density SNP mapping and QTL analysis for time of leaf budburst in Corylus avellana L.

Abstract: The growing area of European hazelnut (Corylus avellana L.) is increasing, as well as the number of producing countries, and there is a pressing need for new improved cultivars. Hazelnut conventional breeding process is slow, due to the length of juvenile phase and the high heterozygosity level. The development of genetic linkage maps and the identification of molecular markers tightly linked to QTL (quantitative trait loci) of agronomic interest are essential tools for speeding up the selection of seedlings c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 84 publications
(101 reference statements)
3
36
1
1
Order By: Relevance
“…This high-throughput and lower cost methodology can then be used to quickly generate genetic linkage maps and identify marker trait associations to answer a broader range of research questions than have traditionally been investigated in the past. In this study, a SNP marker-based ddRADseq genetic linkage map of european hazelnut was created with relatively dense genome coverage similar to other recently developed SNP marker based linkage maps of european hazelnut (Rowley et al, 2018;Torello Marinoni et al, 2018), and then QTL experiments were conducted to specifically determine whether novel or previously known source(s) of EFB resistance QTL were associated with the disease resistance phenotype observed in an environment with high EFB disease pressure (New Jersey location). The putative 'Gasaway' R-gene (as well as resistance from 'Culpl a', 'Crvenje', 'Uebov', OSU 408.040, and OSU 495.072) was previously shown to reside on european hazelnut LG6 (Colburn et al, 2015(Colburn et al, , 2017G€ urcan and Mehlenbacher, 2010;Mehlenbacher et al, 2006;Sathuvalli and Mehlenbacher, 2013;Sathuvalli et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This high-throughput and lower cost methodology can then be used to quickly generate genetic linkage maps and identify marker trait associations to answer a broader range of research questions than have traditionally been investigated in the past. In this study, a SNP marker-based ddRADseq genetic linkage map of european hazelnut was created with relatively dense genome coverage similar to other recently developed SNP marker based linkage maps of european hazelnut (Rowley et al, 2018;Torello Marinoni et al, 2018), and then QTL experiments were conducted to specifically determine whether novel or previously known source(s) of EFB resistance QTL were associated with the disease resistance phenotype observed in an environment with high EFB disease pressure (New Jersey location). The putative 'Gasaway' R-gene (as well as resistance from 'Culpl a', 'Crvenje', 'Uebov', OSU 408.040, and OSU 495.072) was previously shown to reside on european hazelnut LG6 (Colburn et al, 2015(Colburn et al, , 2017G€ urcan and Mehlenbacher, 2010;Mehlenbacher et al, 2006;Sathuvalli and Mehlenbacher, 2013;Sathuvalli et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 126 microsatellite or SSR markers from various sources (Akin et al, 2016;Bassil et al, 2005;Bhattarai and Mehlenbacher, 2018;Boccacci et al, 2005;Colburn et al, 2015Colburn et al, , 2017G€ urcan and Mehlenbacher, 2010;G€ urcan et al, 2010aIves et al, 2014;Mehlenbacher et al, 2006;Sathuvalli and Mehlenbacher, 2013;Sathuvalli et al, 2012) were genotyped as potential anchor markers for LG comparison between the current genetic linkage map and previous maps (Beltramo et al, 2016;Colburn et al, 2015Colburn et al, , 2017G€ urcan et al, 2010a;Ives et al, 2014;Mehlenbacher et al, 2006;Sathuvalli et al, 2011aSathuvalli et al, , 2011bSathuvalli et al, , 2012Torello Marinoni et al, 2018). A prefix indicated that LG was added to the SSR marker names.…”
Section: Microsatellite (Ssr) Markersmentioning
confidence: 99%
See 2 more Smart Citations
“…Although single nucleotide polymorphism (SNP) markers can be generated in large numbers by procedures including genotypingby-sequencing [GBS (Elshire et al, 2011)] and double digest RADseq (Peterson et al, 2012), SSR markers continue to have many research and breeding applications in plants. In hazelnut, for example, € Ozturk et al (2017) studied associations of SSR markers with nut and kernel traits in a Slovenian hazelnut collection, and Marinoni et al (2018) used SSR and SNP markers to identify QTL in a seedling population from 'Tonda Gentile delle Langhe' x 'Merveille de Bollwiller'.…”
Section: Discussionmentioning
confidence: 99%